THE EFFECT OF 0.12% CHLORHEXIDINE DIGLUCONATE AND 0.1% CHLORINE DIOXIDE ON DISCOLORATION OF NANOFILLED COMPOSITE RESIN - Shabika Shabika; Gustantyo Wahyu Wibowo; Ratna Damma Purnawati; Isniya Nosartika (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
ABSTRAK Background: Composite resins are able to generate the color of dental restorative materials based on the original teeth's color. Nanofilled composite resins have compressive strength, good polishing, and color stability compared to other types of composite resins. Color changes may occur due to intrinsic and extrinsic factor example mouthwash. Mouthwash that is commonly used is chlorhexidine. The use of chlorhexidine mouthwash continuously may stain the composite resins. Mouthwash that has a good anti-plaque other than chlorhexidine is chlorine dioxide which has a clear color and does not cause changes in taste on the tongue.Aim: To determine the effect of 0.12% chlorhexidine digluconate mouthwash and 0.1% chlorine dioxide mouthwash to the discoloration of nanofilled composite resins. Methods: This study is an experimental study with a pre-test and post-test control group design. Samples are nanofilledcomposite resins made into discs in total of 27 and divided into three groups with different treatments, soaked with 0.12% chlorhexidine digluconate mouthwash, 0.1% chlorine dioxide mouthwash, and sterile distilled water. Each group was soaked for 24 hours and tested for staining using chromameter.Result: ANOVA test showed the significant difference between group, that the greatest color change is the one soaked with 0.12% chlorhexidine digluconate mouthwash compared to 0.1% chlorine dioxide mouthwashConclusions: The use of 0.1% chlorine dioxide mouthwash does not cause discoloration as much as 0.12% chlorhexidine digluconate mouthwash.Keywords: Chlorhexidine digluconate, Chlorine dioxide, nanofilled composite resin, discoloration